2010
DOI: 10.1002/chem.201000489
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Catalytic Deperoxidation of tert‐Butylhydroperoxide with Cobalt(II) Acetylacetonate

Abstract: The Co(II)/Co(III)-induced decomposition of hydroperoxides is an important reaction in many industrial processes and is referred to as deperoxidation. In the first step of the so-called Haber-Weiss cycle, alkoxyl radicals and Co(III)-OH species are generated upon the reaction of the Co(II) ion with ROOH. The catalytic cycle is closed upon the regeneration of the Co(II) ion through the reaction of the Co(III)-OH species with a second ROOH molecule, thus producing one equivalent of the peroxyl radicals. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 61 publications
(56 reference statements)
0
42
0
4
Order By: Relevance
“…As already well recognised in this review, oxidation of linseed oil involves peroxyl chemistry, displaying importance to other industrial applications, such as that described by Turra et al (Turra et al 2010). These authors reported the mechanism of the decomposition of tertbutylhydroperoxides catalysed by cobalt(II) acetylacetonate (in cyclohexane).…”
Section: Catalytic Mechanism Of Decomposition Of Hydroperoxidesmentioning
confidence: 61%
See 3 more Smart Citations
“…As already well recognised in this review, oxidation of linseed oil involves peroxyl chemistry, displaying importance to other industrial applications, such as that described by Turra et al (Turra et al 2010). These authors reported the mechanism of the decomposition of tertbutylhydroperoxides catalysed by cobalt(II) acetylacetonate (in cyclohexane).…”
Section: Catalytic Mechanism Of Decomposition Of Hydroperoxidesmentioning
confidence: 61%
“…The rate of this deperoxidation decreases at higher cobalt concentration, for instance at 333 K, the rate decreases once the concentration of Co(acac) 2 exceeds 100 μM (Turra et al 2011). The proposed explanation invokes the termination reaction of the Co III -OH to form a stable bis (μ-hydroxo) dimer, Co-(OH) 2 -Co, (Turra et al 2010) as illustrated in the following Scheme 5:…”
Section: Catalytic Mechanism Of Decomposition Of Hydroperoxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Hermans and co-workers comprising both computational and kinetic studies of the autoxidation of cyclohexane by means of UV-Vis spectroscopy suggested that the dominant species is Co II . 153 Additionally, considering a more detailed view of eq.6 in the case of alkanes (either linear, branched or cyclic) this step can lead to the expected partial oxidation products alcohol and ketone at once:…”
Section: Autoxidation Promoted By Metalsmentioning
confidence: 99%